Pharmacist‐driven discontinuation of antipsychotics for ICU delirium: A quasi‐experimental study. Issue 6 (13th April 2020) - Stuart, Misa M.; Smith, Zachary R.; Payter, Katelyn A.; Martz, Carolyn R.; To, Long; Swiderek, Jennifer L.; Coba, Victor E.; Peters, Michael A.
Abstract: Introduction: The use of antipsychotics reduces the duration of intensive care unit (ICU) delirium. Continuation of antipsychotics prescribed for ICU delirium at hospital discharge has been an increasingly reported phenomenon with risk factors for continuation upon discharge identified. Objective: To evaluate a pharmacist‐driven discontinuation protocol on the rate of patients with an antipsychotic continued at hospital discharge for ICU delirium. Methods: This was a single‐center, retrospective quasi‐experimental study of patients admitted to the medical, surgical, or cardiac ICU started on antipsychotics for delirium. A protocol was developed for pharmacists to discontinue scheduled antipsychotics once delirium had resolved. The pre‐ and post‐protocol groups included patients between November 2015 to April 2016 and November 2017 to April 2018, respectively. The primary outcome was the rate of antipsychotic continuation at hospital discharge in the pre‐ and postprotocol groups. Secondary outcomes were related to antipsychotic use and adverse events. Chi‐square, Fisher's exact test, Mann‐Whitney U test, and t ‐test were used as appropriate. Results: A total of 158 patients were included. There were no differences in baseline demographics including age, gender, ICU type, baseline QTc, ICU length of stay (LOS) or hospital LOS (25 [13, 34] vs 19 [13, 30] days; P > .05). There was a significant reduction in the rate of antipsychotics continued at hospital discharge with 26 (32.9%) and 6 (7.6%) patients having therapy continued in the pre‐ and postprotocol groups, respectively ( P < .001). No differences were noted in antipsychotic continuation upon transfer to floor, QTc prolongation, or recurrence of delirium within 7 days of antipsychotic discontinuation. Conclusions: Implementation of a pharmacist‐driven antipsychotic discontinuation protocol for delirium was associated with a significant decrease in antipsychotic continuation at hospital discharge. The protocol did not result in a significantly higher incidence of QTc prolongation or recurrence of delirium. Future studies are needed to assess antipsychotic discontinuation in the ICU setting.